Oil Palm Biomass Sap-Rotten Rice as a Source to Remove Metal Ions and Generate Electricity as By-Products through Microbial Fuel Cell Technology - Anoud Saud Alshammari; Ghada Mohamed Aleid; Alamri Rahmah Dhahawi Ahmad; Asma D. Alomari; Shehu Sa’ad Abdullahi; Rania Edrees Adam Mohammad (Journal of Chemistry)
Microbial fuel cell (MFC) is a new and interesting technology that can be used to treat wastewater without using electricity. The current research focuses on electron generation, which is one of the technique’s major challenges. According to the latest literature, the study was planned to successfully remove the metals from artificial wastewater at high concentrations and generate electricity. On average, after 18 days of operation, it offered 610 mV with 1000 ῼ constant external resistance. The internal resistance was found to be 520 ῼ. The achieved power density was 3.164 mW/m2 at an external resistance of 1000 ῼ. The achieved removal efficiencies of Pb2+, Cd2+, Cr3+, and Ni2+ were 83.67%, 84.10%, 84.55%, and 95.99%, respectively. The operation lasted for 25 days. The cyclic voltameter studies show that there is a gradual oxidation rate of organic substances, while on day 25, the removal efficiency reached its maximum. The specific capacitance was found to be high between days 15 and 20, i.e., 0.0000540 F/g. It also indicated that biofilm was stable around day 18. Furthermore, the biological characterization also demonstrated that MFC operation was very smooth throughout the process, even at high concentrations (100 mg/L) of metal ions. Finally, there is the MFC method, as well as some new challenges and future recommendations.